PENGEMBANGAN LKPD MATEMATIKA BERBASIS PENGUATAN PENDIDIKAN KARAKTER KELAS IV SEKOLAH DASAR NEGERI 2 KALIJAGA TIMUR - Musabihatul Kudsiah; Arif Rahman Hakim; Muh. Yazid; Ardi Sri Lestari (Prodi Pendidikan Matematika FKIP Universitas Madura, 2023)
This study aims to develop a Mathematics Student Worksheet (LKPD) based on character education strengthening using the ADDIE model research design which consists of 5 stages, namely Analyze, Design, Development, Implementation, and Evaluation. This research was conducted on fourth grade students with the number of respondents being 20 students. This research and development instrument uses a validation sheet, and student response questionnaires. The results of the material expert validation test with a total score of 62 and are in the range of X scores > 58.74 with the